Emerging interleukin receptor antagonists for the treatment of asthma. (3rd July 2017) - Al Efraij, Khalid; FitzGerald, J. Mark
ABSTRACT: Introduction : Asthma is a heterogeneous disease, usually characterized by chronic airway inflammation. Most patients with asthma can be well-controlled with inhaled corticosteroids and, if necessary, the addition of a long-acting beta agonist. Despite these therapies, 5% to 10% of patients with asthma have severe, uncontrolled asthma. Selecting patients based on peripheral eosinophil counts and a history of exacerbations has led to significant decreases in exacerbations and an improvement in asthma control with medications that target IL-4, IL-5 and IL-13/. Areas covered : This review will cover the definition of severe asthma, existing treatment options, biomarkers, and the emerging role of interleukin antagonists in the treatment of severe asthma. Expert opinion : IL antagonists are novel drugs targeting important inflammatory cytokines in asthma. Anti-IL-5 drugs provide the most promise as they have obtained regulatory approval and are available for use. Anti-IL-4 drug results are also promising. There is, however, uncertainty regarding the success of anti-IL-13 drugs development at this point. An ongoing focus of research is to significantly increase our understanding of the biology of asthma, and in particular severe asthma, making more and better targeted therapies. There may also be potential in the future to use these new drugs earlier in the development of asthma, as disease-modifying interventions that might be associated with remission or even cure.